IMF Survey, Volume 31, Issue 03. (IMF Survey; IMF Survey ;, 2002)
Following a series of international donor meetings aimed at helping Afghanistan stabilize and rebuild its economy, the IMF sent a mission to Kabul for four days in late January. The team was led by Paul Chabrier, Director of the IMF's Middle Eastern Department. He speaks here about the country's immediate needs and the IMF's role.